Comprehensive Analysis of E3 Ubiquitin Ligases Reveals Ring Finger Protein 223 as a Novel Oncogene Activated by KLF4 in Pancreatic Cancer - Feng, Lei; Wang, Jieqing; Zhang, Jianmin; Diao, Jingfang; He, Longguang; Fu, Chaoyi; Liao, Hui; Xu, Xiaoping; Gao, Yi; Zhou, Chenjie (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic cancer is one of the major malignancies and causes of mortality worldwide. E3 ubiquitin-protein ligases transfer activated ubiquitin from ubiquitin-conjugating enzymes to protein substrates and confer substrate specificity in cancer. In this study, we first downloaded data from The Cancer Genome Atlas (TCGA) pancreatic adenocarcinoma (PAAD) dataset, acquired all 27 differentially expressed genes (DEGs), and identified genomic alterations. Then, the prognostic significance of differentially expressed genes (DEGs) was analyzed, and 8 DEGs (MECOM, CBLC, MARCHF4, RNF166, TRIM46, LONRF3, RNF39 and RNF223) and 2 clinical parameters (pathological N stage and T stage) exhibited prognostic significance. RNF223 showed independent significance as an unfavorable prognostic marker and was chosen for subsequent analysis. Next, the function of RNF223 in the pancreatic cancer cell lines ASPC-1 and PANC-1 was investigated, and RNF223 silencing promoted pancreatic cancer growth and migration. To explore the potential targets and pathways of RNF223 in pancreatic cancer, quantitative proteomics was applied to analyze differentially expressed proteins, and metabolism-related pathways were primarily enriched. Finally, the reason for the elevated expression of RNF223 was analyzed, and KLF4 was shown to contribute to the increased expression of RNF233. In conclusion, this study comprehensively analyzed the clinical significance of E3 ligases. Functional assays revealed that RNF223 promotes cancer by regulating cell metabolism. Finally, the elevated expression of RNF223 was attributed to KLF4-mediated transcriptional activation. This study broadens our knowledge regarding E3 ubiquitin ligases and signal transduction and provides novel markers and therapeutic targets in pancreatic cancer.